#childhoodobesity – A brief literature review of the role of social media in body image shaping and eating patterns among children and adolescents - Modrzejewska, Adriana; Czepczor-Bernat, Kamila; Modrzejewska, Justyna; Roszkowska, Agnieszka; Zembura, Marcela; Matusik, Paweł (Frontiers in Pediatrics, 2022)
Children's food preferences are closely related to their parents' food preferences and knowledge of food is linked to what their parents share with them. Parents, however, are not the only people who model such behavior. Paradoxically, the ubiquitous technological development can also pose a huge threat. In developed countries, 94% of teenagers use social media platforms such as: Instagram, Snapchat, Facebook or TikTok, and this also applies to children. It can therefore be argued that parents' nutritional preferences and behavior are related to the same behaviors of children and there is an extensive literature on this subject. It is therefore important to check how other factors – new technology (and social media in particular) – can influence changes in this area. A literature search was conducted in the following databases: Google Scholar, PubMed, EBSCO in December 2021. After applying all the filters and verification of relevance in terms of the research on the topic of interest to us, 4 articles related to research on body image and social media and 4 articles related to research on food choices and social media among children and adolescents were obtained. The conducted analysis showed that various studies so far indicate that social media can have a very strong influence on the development of eating patterns and body image in children and adolescents, which in turn may be one of the risk factors for developing obesity when promoted behaviors are not associated with a healthy lifestyle. It is also worth pointing out that social media can be used as a resource in the prevention and treatment of obesity. A closer look at this topic seems to be particularly important due to the fact that, among adults, social media is not only a very important source of information about lifestyle, but also a source of social support when people attempting to lose weight. Therefore, by increasing preventive activity in social media and using modern solutions related to social media (including the use of hashtag signs), we can have a greater impact on the health awareness of children and adolescents around the world.